Micro, Small and Medium Enterprise Development (MSMEs) Strategies Through Business Digitalization in The Face Of Global Competition - Bambang Riyadi; Giyah Yuliari; Putra Perdana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
In the era of globalization, every country will try to win the competition in various ways. The development of digital technology is a way and opportunity for Micro, Small and Medium Enterprises (MSMEs.) However, not all MSME players are ready to do business digitally, both in marketing and finance. The phenomenon that has occurred lately is evidence that the drastic decline in sales turnover of MSME products is due to one of them shifting the offline sales system to online sales. MSMEs must be able to adapt to technological changes, which cannot be stopped. The most important change is to provide human resources engaged in MSMEs with understanding, knowledge and skills to use digital systems. Through collaboration between MSME actors, government authorities and academics, technical guidance and training can be carried out massively and systematically, so that these activities can answer the needs of MSMEs to compete not only in the local market but also in the global market. This writing begins with research that uses qualitative descriptive research methods. Data collection techniques used interviews, observation, document analysis, case studies and focus group discussions. The data used qualitative data analyzed using approaches such as content analysis, narrative analysis.